Análise qualitativa da atuação dos peritos psicólogos em casos de suspeita de abuso sexual em disputas de guarda - Pacheco, Maria da Graça (2018)
The present study investigated the way of psychologists proceed in the evaluation of cases involving allegations of sexual abuse, committed against children and adolescents, in the intrafamilial context in custody. Five psychologists were interviewed. A content analysis was conducted aiming to identify relevant topics in the participants' speeches. The results demonstrated that it was not possible to find a consensus among the participants on the choice of methods and procedures adopted in the evaluations. Some expert psychologists have described to use their own methods of evaluation, often without a technical-scientific foundation. In addition, the participants demonstrated to understand subjects such as parental alienation, evaluation of the credibility of the victim's report and false memories in a different way which may impair the investigative character of the expertise. Further studies are indicated for a better understanding of the issue.